Oral microbiota in oropharyngeal cancers: Friend or foe? - Nocini, Riccardo; Muzio, Lorenzo Lo; Gibellini, Davide; Malerba, Giovanni; Milella, Michele; Chirumbolo, Salvatore; Zerman, Nicoletta (Frontiers in Oncology, 2022)
Abstract Oral microbiome is a complex population of micro-organisms, which by cross-talking with the local immune system, plays a major role in the immune homeostasis of the oral cavity, further contributing in the physiology of the gastro-intestinal microbiota. Understanding their involvement in the onset and pathogenesis of oropharyngeal cancers is paramount, despite very few reports deal with the fundamental role exerted by oral microbiota disorders, such as dysbiosis and impairment in the oral microbiome composition as causative factors in the development of oropharyngeal tumors. Current research, via metabolomic or meta-transcriptomic analyses, is wondering how this complex microbial population regulates the immune homeostasis in oral and pharyngeal mucosa and whether changes in bacterial composition may give insights on the role of oral microbiome in the development of oropharyngeal tumors, so to prevent their occurrence.